El back charge en los contratos de construcción. Su configuración en la praxis transaccional internacional - Vásquez Rebaza, Walter (2023)
This work addresses, from a legal perspective, a legal remedy specific to construction contracts that has significant practical applicability in contemporary projects: the back charge. Despite its importance, the understanding of the back charge as a contractual instrument and as a private legal remedy is still quite limited, resulting in significant gaps in legal knowledge on the subject in Peru and, in general, in civil law jurisdictions. In light of this reality, this legal research article proposes a basic configuration of the back charge, its concept, characteristics, and standard operation, as well as its main practical and dysfunctional aspects. It also examines whether the Peruvian Civil Code recognizes any similar legal remedy. Furthermore, guidelines are outlined for the balanced incorporation of this concept into contemporary construction contracts. To achieve these purposes, this research takes into account the configuration of the back charge in private contemporary construction contracts with an international focus, in which the legal remedy in question originates voluntarily (i.e., derived from the private autonomy of the parties), sometimes considering international standard contractual models (such as FIDIC and NEC).